Biliary fistula after pancreaticoduodenectomy: data from 1618 consecutive pancreaticoduodenectomies. Issue 3 (March 2017) - Andrianello, Stefano; Marchegiani, Giovanni; Malleo, Giuseppe; Pollini, Tommaso; Bonamini, Deborah; Salvia, Roberto; Bassi, Claudio; Landoni, Luca
Abstract: Background: Biliary fistula (BF) occurs in 3–8% of patients following pancreaticoduodenectomy (PD). It usually pursues a benign course, but rarely may represent a life-threatening event. Study design: Data from 1618 PDs were collected prospectively. BF was defined as the presence of bile stained fluid from drains by post-operative day 3 and confirmed by sinogram in the majority of cases. Three classifications were validated. Results: BF occurred in 58 (3.6%) patients. In 22 cases was associated with pancreatic fistula (POPF). POPF, PPH, operative time and a smaller common bile duct (CBD) were significantly associated with BF. Only CBD diameter (HR 0.55, CI 95% 0.44–0.7, p < 0.01) was an independent predictor of BF. Patients with smaller CBDs developing concomitant BF and POPF carried the highest mortality rate (34.8%, n = 8/22). All the existing classifications resulted in discrete categories of BFs when considering hospital stay and total cost as dependent variables. Conclusions: Biliary fistula is rare, but it can be life threatening when associated with POPF. As the sole independent risk factor is the CBD diameter, surgical technique is crucial. Regardless of the existing classification systems, further studies must assess the additive burden of BF when a concomitant POPF is present.